The Integration of Artificial Intelligence in Hadith Scholarship: A Bibliometric Perspective on Emerging Research Directions - Azwar, Azwar; Abur Hamdi Usman; Mohd Farid Ravi Abdullah; Mutsalim Khareng; Lilly Suzana Shamsu (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2025)
This study aims to map the research landscape concerning the role of artificial intelligence (AI) in hadith studies. It seeks to identify key academic trends, including publication growth patterns, frequently explored topics, institutional and individual contributions, emerging research directions, and areas that remain underexplored. The analysis employs bibliometric methods based on data from the Scopus database, covering the period from 2013 to 2024. The findings reveal a significant increase in scholarly interest, with 103 publications identified, reflecting the growing recognition of AI's relevance in hadith scholarship. Among the most prolific contributors is Sayoud, H., while the most cited work—Hadith Data Mining and Classification: A Comparative Analysis by Saloot M.A. et al. (2021)—highlights the multidisciplinary importance of AI in the classification of hadith. Publication analysis shows that the Journal of Theoretical and Applied Information Technology, Lecture Notes in Computer Science, and Procedia Computer Science are the leading platforms for disseminating AI-related research in this domain. Universiti Kebangsaan Malaysia stands out as the most active institution in this field. Geographically, Malaysia leads the research output, contributing 30 publications. Topic mapping identifies key research themes such as hadith, authenticity, narrator, Qur'an, model, approach, technique, and classifier. Emerging topics—including authenticity, narrator, reliability, isnad (chain of transmission), saying, and deep learning—indicate a growing focus on hadith authentication and chain analysis using AI technologies. Conversely, areas such as complexity, challenge, meaning, phase, order, Muslim, and legislation appear to be underrepresented, suggesting potential opportunities for future exploration. This study highlights the growing integration of AI into hadith scholarship, urging institutions to adopt digital approaches, expand research collaboration, and explore underrepresented topics through broader datasets and mixed-method analyses to advance both theoretical and practical dimensions of Islamic studies.